The plain input gray scale images: (a) Bride; (b); Chair (c) Flowers; (d) Hailstones. - Nayeem Ahmad Khan (11727377) (2025)
The plain input gray scale images: (a) Bride; (b); Chair (c) Flowers; (d) Hailstones.